Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00590-015-1665-7
|View full text |Cite
|
Sign up to set email alerts
|

Are titanium-on-titanium TiAl6V4 modular necks safe in total hip arthroplasty for non-overweight patients? Results of a prospective series at a minimum follow-up of 7 years

Abstract: Using extramedullar modularity in total hip arthroplasty has been proposed as an option to optimize the restoration of hip biomechanics. To avoid the problems that were observed with cobalt-chrome modular neck, titanium modular necks have been developed. The goals of our study were to evaluate the safety of titanium-on-titanium TiAl6V4 modular neck system. Hundred patients with a mean age of 69.6 ± 10.6 (42-86 years) and mean BMI of 25.07 ± 4.86 (17-38 kg/m(2)) suffering from primary or secondary arthritis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…14 studies met the final criteria to be included in the systematic review. 2134 Notably, 3 studies were excluded as they evaluated recalled implant designs. 3537 The majority of papers included were case series ( n = 12) with the remaining two studies being national joint registry studies that included data on modular implants (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 studies met the final criteria to be included in the systematic review. 2134 Notably, 3 studies were excluded as they evaluated recalled implant designs. 3537 The majority of papers included were case series ( n = 12) with the remaining two studies being national joint registry studies that included data on modular implants (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) was an indication for THA in 6 studies and was the exclusive indication for surgery in 1 of these. 4 studies included a comparator group of patients who underwent fixed-neck THA (Table 3) 2134 and (Table 4). 2134,39,40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian Orthopaedic Association National Joint Replacement Registry reported exchangeable neck stem THAs have a higher rate of revision (almost twice) at 10 years compared with fixed neck stem THAs, in patients with osteoarthritis, regardless of the bearing surface [2]; Meftah et al [33] also found a high cumulative revision rate with one specific model of exchangeable neck THA, but did not have a comparison group with fixed neck THA. Others found no difference [17, 18, 43, 50]. Except for the Australian registry from a population-based cohort (albeit one in which data on patients’ medical histories are limited), all other studies on this topic have been performed on small cohorts and often without a comparative group of fixed neck THAs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as femoral necks and stems of these prosthetic models are separated elements, this leads to the presence of additional coupling interactions. This junction might be a spot with a greater risk of complications, even if more recent studies have shown that the responsibility for most of the failures related to these components is to be attributed to the materials (i.e., Co-Cr) rather than the prosthetic design [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%